👤

8.Calculati:
e) [tex] (1,2^{2} ) ^{-1} [/tex]
f) [tex] [(-0,3)^{3} ] ^{-1} [/tex]
g) [tex] [(0,1)^{-1} ] ^{-4} [/tex]
h) [tex][(1 \frac{1}{3} ) ^{2} ] ^{-1} [/tex]

Ma poate ajuta cineva?


Răspuns :

[tex]\displaystyle e).(1,2^2)^{-1}=(1,44)^{-1}=\left( \frac{144}{10} \right)^{-1}= \frac{10}{144}= \frac{5}{72} [/tex]

[tex]\displaystyle f).[(-0,3)^3]^{-1}=(-0,027)^{-1}=\left(- \frac{27}{1000} \right)^{-1}=- \frac{1000}{27} [/tex]

[tex]\displaystyle g).[(0,1)^{-1}]^{-4}=\left[\left( \frac{1}{10} \right)^{-1}\right]^{-4}=10^{-4}= \frac{1}{10^4} = \frac{1}{10000} [/tex]

[tex]\displaystyle h). \left[\left(1 \frac{1}{3} \right)^2 \right]^{-1}=\left[\left( \frac{4}{3} \right)^2\right]^{-1}=\left( \frac{4^2}{3^2} \right)^{-1}=\left( \frac{16}{9} \right)^{-1}= \frac{9}{16} [/tex]
[tex] ( a^{ m})^{n} = a^{m*n} [/tex]

e).  [tex] [(1.2)^{2}] ^{-1} [/tex]=[tex] (1,2)^{-2}[/tex]=[tex] \frac{1}{ (1,2)^{2} } = \frac{1}{1.44} = 0,69(4)[/tex]


f).[tex] [(0.3)^{3}] ^{-1} [/tex]=[tex](-0,3)^{-3}=\frac{1}{ (-0.3)^{3} } = \frac{1}{-0.027} = -37.(037)[/tex]


g).[tex][ (0,1)^{-1}]^{-4} [/tex]=[tex](0,1)^{4}=0,0001[/tex]


h).[tex] [ (1 \frac{1}{3})^{2} ]^{-1} [/tex]=[tex]( \frac{4}{3} )^{-2}=\frac{1}{ ( \frac{4}{3} )^{2} } = \frac{1}{ \frac{16}{9} } = \frac{1}{1}* \frac{9}{16}= \frac{9}{16} =0.5625 [/tex]


( [tex] 1 \frac{1}{3} = \frac{1*3 + 1}{3} = \frac{4}{3} [/tex]  am introdus intregii in fractie )